Pengaruh Media Pop Up Book Terhadap Retensi (Daya Ingat) Siswa Pada Mata Pelajaran Pai Kelas Iii Sd Negeri 04 Kubang Putiah - Rahmadani, Nur Rizki; Rahman, Yulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effect of pop-up book media on student retention (memory). This research is an experimental quantitative research, quantitative research is a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what we want to know. By using the One group pretest posttest Design research design, namely an experiment carried out on one group only without a comparison group. This design is a development of the One Shot Case Study Design, namely by conducting one measurement in front (pretest) before the treatment (treatment) and after that another measurement (posttest) is carried out. The results of this study prove that there is an influence of Pop Up Book media on retention (memory) by obtaining the results of the sig. (2-tailed) hypothesis test of (0.000) which means that the significance is smaller than (0.05) or sig. (2-tailed) (0.000) < sig. (0.05). The average N-Gain is as follows: recall is 0.50 medium criteria, recognition aspect is 0.46 medium criteria, reintegrative aspect is 0.20 low criteria, overall pretest to posttest is 0.45, where medium criteria are obtained. With the acquisition of t count 8.167 > t table 2.086 H0 is rejected H1 is accepted so it can be concluded that there is an influence of Pop Up Book media on retention (memory) of grade III students of Elementary School 04 Kubang Putiah. So this media is considered effective in increasing student retention (memory) in each aspect, namely recall, recognition, and reintegrative.